2020
DOI: 10.3390/polym12102215
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Repetitive Square Voltage Duty Cycle on the Electrical Tree Characteristics of Epoxy Resin

Abstract: The application of wide band-gap power electronic devices brings more challenges to insulating packaging technology. Knowing the influence of applied voltage parameters on insulation performance is helpful to evaluate the insulation condition of electric power equipment. In this paper, the effect of repetitive square wave voltage duty cycle on the growth characteristics of electrical trees in epoxy resin was studied. The experimental results show that the square wave voltage duty cycle has a significant influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Power electronic equipment is generally operated under high-frequency pulse voltages for long periods. On the one hand, the power electronic technology, such as pulse width modulation (PWM), is applied to realise flexible control of electronic equipment by subjecting to a high-frequency pulse voltage [3,4]. For example, the power electronic transformer is a new type of transformer that combines the power electronic technology with a high frequency transformer.…”
Section: Introductionmentioning
confidence: 99%
“…Power electronic equipment is generally operated under high-frequency pulse voltages for long periods. On the one hand, the power electronic technology, such as pulse width modulation (PWM), is applied to realise flexible control of electronic equipment by subjecting to a high-frequency pulse voltage [3,4]. For example, the power electronic transformer is a new type of transformer that combines the power electronic technology with a high frequency transformer.…”
Section: Introductionmentioning
confidence: 99%
“…In experimental studies, extensive efforts have been made to obtain the partial discharge characteristics of power electronics [9,10], the surface charge characteristics [11][12][13], the streamer characteristics [14], accumulation and dissipation of the space charge characteristics [15,16] of engineering insulation materials. Significant progress has been achieved to investigate the dependence of waveform parameters of the PPSW voltage on space charge accumulation characteristics [17], partial discharge characteristics [18], surface discharge characteristics [19], and electric tree characteristics [20,21] of insulation materials. Besides, polarisation characteristics of double-layer composites under the square waveform voltage with only one single cycle were also studied [22].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, nanodielectric insulating materials have received a lot of attention in the global market [19][20][21][22]. Several published studies proclaim that polymers and their derived nanocomposite insulating materials can enhance the dielectric properties for electrical applications [23][24][25][26][27][28][29]. In another study, fluorine-coated PI films have shown promising improvements in results by applying a thin layer of conductive surface coating on the top and bottom of these films [30,31].…”
Section: Introductionmentioning
confidence: 99%